Factors That Influence Canteen Conditions of Elementary Schools in Semarang City (Universitas Negeri Semarang, 2020)
Healthy canteens must provide food and drinks that are guaranteed safety, nutrition and have safe, clean and healthy facilities for all school residents. The purpose of this study was to analyze the factors that influence the condition of the canteen in Elementary Schools of Semarang City. Type of analytic observational research. This study used a cross sectional design. Retrieval of data was using questionnaire instruments and observation sheets. Data analysis used chi square and logistic regression. The results of data analysis there was an influence between the level of knowledge of the canteen condition (pv = 0.006), there was an influence between the level of education on the canteen condition (pv = 0.005), there was no effect between training on the canteen condition (pv = 0.972), there was an influence between the availability of media the mass of the canteen condition (pv = 0.018), there was no influence between the accreditation status of the canteen condition (pv = 0.72). In conclusion, there was the influence of knowledge, level of education, and the availability of mass media on the condition of the canteen and there were two factors that do not affect such as the training and accreditation status of the canteen. The most influential factor was the availability of mass media. A healthy canteen condition will have an impact on the health of school residents and for elementary school students, a healthy canteen will support good growth and development.